Soccer skill development in talented players - Huijgen, B. C. H.; Elferink-Gemser, M. T.; Ali, A.; Visscher, C. (International Journal of Sports Medicine, 2013)
The aim of the study was to gain insight into the development of soccer-specific skills and whether differences between talented players exist on the Loughborough Soccer Passing Test (LSPT). Two scores were derived from the LSPT: 1) execution time: time to complete 16 passes (speed) and 2) skill performance time: execution time including bonus and penalty time for accuracy. The study consisted of 2 parts, the first of which incorporated a quasi-longitudinal design with 270 talented players aged 10-18 years performing the LSPT (661 measurement occasions); multilevel modelling was applied. Secondly, differences between those players allowed to continue in the development program (selected, n=269) and players who were forced to leave (de-selected, n=50) were investigated using independent sample t-tests. The longitudinal data showed that the predicted execution time (i. e., speed) improved approximately 18% from age 10-18 years (P<0.05), skill performance time (i. e., combination of speed and accuracy) was predicted to improve approximately 32% (P<0.05). The second part showed that selected players outscored de-selected players only on skill performance time (P<0.05), not on execution time (P>0.05). In conclusion, in high-level youth soccer, the combination of speed and accuracy in soccer skills might be more important than speed alone.